2013
DOI: 10.1063/1.4774382
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field effect on coercivity distributions in FePt magneto-electric devices

Abstract: International audienceWe have investigated the contribution of stochastic thermally activated processes to the electric-field effects on coercivity in FePt. Coercive field distributions were measured under different gate voltages in solid-state field-effect structures. For low voltages a shift in the coercive field distribution can be observed, however, it is not larger than the width of the distribution. Higher oltages are needed to obtain the splitting from the negative (zero) voltage distribution allowing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…24 However, as seen in Fig. 3, the electric-field effect in coercivity that can be observed using HfO 2 (a) and ZrO 2 /HfO 2 (b) dielectric layers is completely suppressed when using Al 2 O 3 .…”
mentioning
confidence: 97%
“…24 However, as seen in Fig. 3, the electric-field effect in coercivity that can be observed using HfO 2 (a) and ZrO 2 /HfO 2 (b) dielectric layers is completely suppressed when using Al 2 O 3 .…”
mentioning
confidence: 97%
“…7,15,16 It is reported that the as-deposited FePt film exhibits a facecentered cubic (FCC) structure with soft ferromagnetic properties. Subsequent thermal annealing leads to a phase transformation from disordered FCC structure to ordered and magnetically hard FCT structure.…”
mentioning
confidence: 99%
“…1) Since then, the field effect has been studied in various types of ferromagnetic material. Recent progress in gating technology that uses high-k dielectrics, ferroelectric insulators, and electrolytes has made it possible to modify the magnetic properties of materials with a metallic carrier concentration such as 3d metals, 2,3) their alloys, [4][5][6][7][8] and oxides. 9,10) These electrically tunable magnetic devices are promising because, in addition to their added functionality, their simple architecture is compatible with current semiconductor technologies.…”
mentioning
confidence: 99%